Determination of non-isothermal crystallization rate constant for pseudo-experimental calorimetric data - Galera,Viviane Verona (2009)
In the present work, non-isothermal crystallization data in the form of heat flow vs. temperature curves were generated using the Nakamura Model and its typical parameters reported in the literature for polypropylene. The values obtained for these curves were added to experimental baselines of a DSC to introduce typical noises in the calorimetric traces generated. The Master Curve Approach was applied by one of the authors to retrieve the non-isothermal crystallization rate constant for these simulated curves without information about the conditions used to generate these pseudo-experimental curves. Thus, the applicability of the Master Curve Approach was tested for data perfectly described by the Nakamura Model. With this procedure, the authors were able to check the sensitivity of the method to uncertainties in the determination of the induction time. The results showed good agreement between the pseudo-experimental curves and the curves simulated using the retrieved non-isothermal crystallization rate constant. However, this good agreement was only possible due to a compensation effect, because some of the parameters showed significant differences between the pseudo-experimental and retrieved values. Among these parameters are the pre-exponential factor of the non-isothermal crystallization rate constant, the temperature of the onset of the crystallization process, and the initial degree of crystallinity of the differential form of the Nakamura Model. These problems were not caused by the Master Curve Approach, but by inherent difficulties in the DSC analysis.